2020
DOI: 10.1002/aoc.5815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral analysis and in vitro cytotoxicity of diorganotin (IV) complexes derived from indole‐3‐butyric hydrazide

Abstract: A series (1–20) of diorganotin (IV) complexes with general formula R2SnL were formed by the reaction of R2SnCl2 (where R = Me, Et, Bu and Ph) with Schiff base ligands (H2L1–4) derived from the reaction of indole‐3‐butyric hydrazide with the salicylaldehyde and its derivatives. The structure elucidation of compounds were done by using UV–Vis, FT‐IR, NMR (1H, 13C, 119Sn), Mass spectrometry and thermal gravimetric analysis. Spectroscopic evidences suggested tridentate nature (ONO) of Schiff base ligands and coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 61 publications
1
31
0
1
Order By: Relevance
“…Also, the spectrum of the zinc complex showed two vibrations bands, ν (M–S) at 330 cm −1 and ν (M–Br) at 270 cm −1 , which corresponded to coordination bonds. [ 4,17,34 ] The same differences were observed when passing from the ligand ( L ) to [CdCl 2 (MTSVT) 2 ] ( 3 ) and [CdBr 2 (MTSVT) 2 . H 2 O] ( 4 ).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Also, the spectrum of the zinc complex showed two vibrations bands, ν (M–S) at 330 cm −1 and ν (M–Br) at 270 cm −1 , which corresponded to coordination bonds. [ 4,17,34 ] The same differences were observed when passing from the ligand ( L ) to [CdCl 2 (MTSVT) 2 ] ( 3 ) and [CdBr 2 (MTSVT) 2 . H 2 O] ( 4 ).…”
Section: Resultsmentioning
confidence: 52%
“…[ 34–36 ] However, the N1–N2 [1.380(18) Å] and N2–C2 [1,348(2) Å] bond distances observed are intermediate between the ideal values of the corresponding single [N–N, 1.45 Å; C–N, 1.47 Å] and double bonds [N=N, 1.25 Å; C=N 1.28 Å], which are in support of an extended π delocalization along the thiosemicarbazone chain. [ 4,35 ] The sulfur atom S1 and the nitrogen atom of the imine N3 are in trans position relative to the C1–N2 bond. This configuration is stabilized by the presence of an intermolecular hydrogen bond (Figure S1 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get a deeper insight concerning the coordination mode of Cu II with 1 , a new titration was performed by using 1 H NMR spectroscopy. Owing to the paramagnetic nature of Cu II , the diamagnetic ion Zn II was used as a model, as several reports show that the coordination mode and stoichiometry should not vary substantially between these two ions …”
Section: Resultsmentioning
confidence: 99%
“…Devi et al (2020) reported a series of diorganotin(IV) compounds derived from the reaction of indole-3-butyric hydrazide with salicylaldehyde and its derivatives (Scheme 1). The hydrazone Schiff base ligands were as follows:Nʹ-(2-hydroxybenzylidene)-4-(1H-indole-3-yl) butanehydrazide [H 2 L 1 ], Nʹ-(2-hydroxy-5 nitrobenzylidene)-4-(1H-indole-3-yl)butanehydrazide [H 2 L 2 ], Nʹ-(5-diethylamino)-2 hydroxybenzylidene-4-(1H-indole-3-yl) butanehydrazide [H 2 L 3 ], and Nʹ-(3,5-dibromo-2 hydroxybenzylidene)-4-(1Hindole-3-yl)butanehydrazide [H 2 L4 ].…”
mentioning
confidence: 99%